Measurement of Corrosion Rate in Storage Tank of Crude Oil - مفتن, صلاح صبار; هويني, مصطفى ستار (Journal of Petroleum Research and Studies, 2024)
The aim of this work is to measure and analyze corrosion problems in storage tanks to find solutions. ASTM A283-C specimens are used for studying the corrosion rate of tank bottoms by two factors of crude oil: the first is salt content, and the other is sulfur percentage. Also, some specimens were coated with a special epoxy to determine the efficiency of corrosion resistance. The specimens immersed in crude oil with a high sulfur content suffered from a high corrosion rate. The maximum corrosion rates of every specimen were calculated, which at the sulfur percentage (5.4399 wt%) as corrosive medium were equal (2.49395 mm/year). While the other specimens for salt content did not suffer from any significant corrosion during the immersion period (six months), the coated specimens with epoxy were not affected by any corrosion.